Fingolimod confers neuroprotection through activation of Rac1 after experimental germinal matrix hemorrhage in rat pups. Issue 5 (2nd February 2017) - Rolland, William B.; Krafft, Paul R.; Lekic, Tim; Klebe, Damon; LeGrand, Julia; Weldon, Abby Jones; Xu, Liang; Zhang, John H.
Abstract: Fingolimod, a sphingosine‐1‐phosphate receptor (S1PR) agonist, is clinically available to treat multiple sclerosis and is showing promise in treating stroke. We investigated if fingolimod provides long‐term protection from experimental neonatal germinal matrix hemorrhage (GMH), aiming to support a potential mechanism of acute fingolimod‐induced protection. GMH was induced in P7 rats by infusion of collagenase (0.3 U) into the right ganglionic eminence. Animals killed at 4 weeks post‐GMH received low‐ or high‐dose fingolimod (0.25 or 1.0 mg/kg) or vehicle, and underwent neurocognitive testing before histopathological evaluation. Subsequently, a cohort of animals killed at 72 h post‐GMH received 1.0 mg/kg fingolimod; the specific S1PR1 agonist, SEW2871; or fingolimod co‐administered with the S1PR1/3/4 inhibitor, VPC23019, or the Rac1 inhibitor, EHT1864. All drugs were injected intraperitoneally 1, 24, and 48 h post‐surgery. At 72 h post‐GMH, brain water content, extravasated Evans blue dye, and hemoglobin were measured as well as the expression levels of phospho‐Akt, Akt, GTP‐Rac1, Total‐Rac1, ZO1, occludin, and claudin‐3 determined. Fingolimod significantly improved long‐term neurocognitive performance and ameliorated brain tissue loss. At 72 h post‐GMH, fingolimod reduced brain water content and Evans blue dye extravasation as well as reversed GMH‐induced loss of tight junctional proteins. S1PR1 agonism showed similar protection, whereas S1PR or Rac1 inhibition abolished the protective effect of fingolimod. Fingolimod treatment improved functional and morphological outcomes after GMH, in part, by tempering acute post‐hemorrhagic blood–brain barrier disruption via the activation of the S1PR1/Akt/Rac1 pathway. Abstract : Neonatal germinal matrix hemorrhage (GMH) often results in lasting deficits. This study aimed to determine the protective effect of fingolimod‐induced sphingosine‐1‐phosphate receptor (S1PR) modulation after experimental GMH. Fingolimod reduced long‐term markers of brain injury. Acute protective effects were dependent on functionality of S1PRs and Rac1. This study supports manipulation of S1PRs and the Rac1 pathway as potentially protective clinical strategies.